Law, life, and lore : it's too late to stop now / Allan C. Hutchinson. - Hutchinson, Allan C., 1951- (Cambridge University Press, 2018)
Law is best interpreted in the context of the traditions and cultures that have shaped its development, implementation, and acceptance. However, these can never be assessed truly objectively: individual interpreters of legal theory need to reflect on how their own experiences create the framework within which they understand legal concepts. Theory is not separate from practice, but one kind of practice. It is rooted in the world, even if it is not grounded by it. In this highly original volume, Allan C. Hutchinson takes up the challenge of self-reflection about how his upbringing, education, and scholarship contributed to his legal insights and analysis. Through this honest examination of key episodes in his own life and work, Hutchinson produces unique interpretations of fundamental legal concepts. This book is required reading for every lawyer or legal scholar who wants to analyse critically where he or she stands when they practice and study law.